2005
DOI: 10.1093/geront/45.6.747
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Adaptation to Visual Impairment and Its Relationship to Depressive Affect in Older Adults With Age-Related Macular Degeneration

Abstract: These findings support the contention that depressive symptomatology as measured by self-report in older adults with ARMD is mediated by one's perceived sense of individual control as it relates to intrapersonal factors underlying adaptation to profound vision loss in old age caused by ARMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
65
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 19 publications
9
65
0
Order By: Relevance
“…Better adjustment as measured by the Adaptation to age-related Vision Loss scale (AVL) was significantly correlated with fewer depressive symptoms in an elderly sample of people with mixed visual impairments 12 and in individuals with age-related macular degeneration (AMD). 13 Results of the current study add to these findings by indicating that depression is associated with poorer adjustment to vision loss, independently of the severity of vision loss (as assessed by a range of clinical visual function tests) and the degree of functional limitations. Therefore, patients with greater depressive symptoms are more likely to be less well adjusted irrespective of the degree of visual impairment and the functional limitations that vision loss causes.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Better adjustment as measured by the Adaptation to age-related Vision Loss scale (AVL) was significantly correlated with fewer depressive symptoms in an elderly sample of people with mixed visual impairments 12 and in individuals with age-related macular degeneration (AMD). 13 Results of the current study add to these findings by indicating that depression is associated with poorer adjustment to vision loss, independently of the severity of vision loss (as assessed by a range of clinical visual function tests) and the degree of functional limitations. Therefore, patients with greater depressive symptoms are more likely to be less well adjusted irrespective of the degree of visual impairment and the functional limitations that vision loss causes.…”
Section: Discussionsupporting
confidence: 65%
“…Although originally designed to be used in the elderly, the GDS has also been validated in younger samples. 35,36 The GDS was chosen primarily based on its previously demonstrated favorable psychometric properties, 37 including evaluations using item response theory 38,39 and its wide use in samples with visual impairment (e.g., Tolman et al 13 ; Brody et al 40 ; Rovner et al 41 ). Within the current sample the GDS was sufficiently unidimensional (first contrast eigenvalue 1.80), demonstrating acceptable fit statistics (MNSQ infit 0.98 6 0.19, outfit 0.99 6 0.38) and had good item (3.48) but not person (1.11) reliability.…”
Section: Adjustment To Vision Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Available research suggests that sensory rehabilitation programs addressing either vision or hearing loss have a positive impact on their adult clients. In one study of adult aural rehabilitation clients in Nigeria, Olusanya 84 [86][87][88] …”
Section: Dual Sensory Loss and Social Interactionmentioning
confidence: 99%
“…In the next decades, the aging of the population will lead to an increase in the number of visually impaired elderly persons [2,3]. Previous research showed that vision loss has a profound impact on daily functioning [4][5][6] and quality of life [7][8][9][10], as indicated by an impaired functional ability and psychological distress [11][12][13]. In addition, visually impaired elderly persons per ceive restrictions in participation [14,15] and participate less in household activities, sports activities and recreational activities as compared to peers [14].…”
Section: Introductionmentioning
confidence: 99%